Teacher Responses to Anxiety in Children Questionnaire (TRAC): psychometric properties and relationship with teaching staff characteristics. Issue 2 (3rd April 2018) - Allen, Jennifer L.; Lerman, Rebecca
ABSTRACT: This study describes the development and evaluation of a new measure, the Teacher Responses to Anxiety in Children (TRAC) questionnaire in 74 primary school teachers. TRAC presents 9 hypothetical scenarios in which a child displays generalized anxiety/worry, social anxiety or separation anxiety symptoms. Teachers rate each scenario on six subscales that reflect different ways of responding to child anxiety. Overall, TRAC showed good internal reliability, with factor analytic results suggesting that it assesses three factors: Autonomy-Promoting, Anxiety-Promoting and Reward responses. Male teachers were significantly more likely than female teachers to use Anxiety-Promoting responses. More experienced teachers reported significantly more reinforcement of anxious avoidance than less experienced teachers, and teaching assistants reported significantly fewer overprotective responses. Teaching staff reported significantly more Autonomy-Promoting responses in social anxiety or generalised anxiety/worry scenarios compared to separation anxiety scenarios. Findings are discussed in terms of their implications for teacher training in the management of child anxiety.